HEALTH FACILITY AND INFRASTRUCTURE MANAGEMENT: A LITERATURE REVIEW APPROACH TO INFRASTRUCTURE AND MEDICAL EQUIPMENT MANAGEMENT FOR OPERATIONAL EFFICIENCY AND SUSTAINABILITY OF MODERN HEALTH SERVICES - Hotmaria Hertawaty Sijabat; Gunawan Widjaja (Adisam Publisher, 2025)
Health facility and infrastructure management in Indonesia, with a focus on managing infrastructure (backup power systems, HVAC, clean water, hazardous waste) and medical equipment (ventilators, ultrasound machines, defibrillators) to achieve operational efficiency of up to 25% and the sustainability of modern services, using the PRISMA approach on the Garuda, Sinta, Neliti, and Scopus databases for the period 2019-2025, based on PMK Regulation No. 43/2019 IPSRS and MFK Regulation No. 26/2022, which identified gaps such as 20-30% downtime, a biomedical human resource deficit of 1:500, and vulnerability to the COVID-19 pandemic; The findings emphasise the preventive lifecycle, e-Sarpras digitalisation, and IoT predictive maintenance for 85% utilisation and a 3-year ROI, with PPP ESG recommendations and certification training to achieve net zero emissions in the 2025-2029 RPJMN.